Chasing sunsets : book 2 in the angels walking series - Kingsbury, Karen (New York : Howard Books, 2015)
Though Mary Cathering loves her wealthy parents, their lifestyle never appealed to her. Instead, Mary Catherine pursues meaning through charity work, giving away a part of herself but never giving away her heart.
Includes discussion questions (3 unnumbered pages)
Keywords: Miracles -- Fiction; Life change events -- Fiction; Christian fiction; Love stories